2008
DOI: 10.1248/cpb.56.1431
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Up Studies on High Shear Wet Granulation Process from Mini-Scale to Commercial Scale

Abstract: 1431Recently the importance of QbD (Quality by design) in International Conference on Harmonisation (ICH) Q8 has been highlighted, 1) and scientific levels of formulation designing and manufacturing designing are more and more emphasized. In addition, there is pressure on the pharmaceutical industry in shortening the development time of new products. Further, considering current situation that there are cases where levels of formulation study and scale-up study, prerequisites of validation, are not sufficient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Scale‐up of high‐shear wet granulation (HSWG) process is of high relevance to the pharmaceutical and food industries. The topic has been a subject of extensive research over the years and many publications exist to date on different ways to scale up this process . The various scale‐up methodologies presented in literature can be broadly classified into two main categories: one that applies fixed mathematical rules to process parameters based on engineering principles from one scale to the other, and the other that empirically adjusts process parameters as needed to maintain the same granule attributes across scales.…”
Section: Introductionmentioning
confidence: 99%
“…Scale‐up of high‐shear wet granulation (HSWG) process is of high relevance to the pharmaceutical and food industries. The topic has been a subject of extensive research over the years and many publications exist to date on different ways to scale up this process . The various scale‐up methodologies presented in literature can be broadly classified into two main categories: one that applies fixed mathematical rules to process parameters based on engineering principles from one scale to the other, and the other that empirically adjusts process parameters as needed to maintain the same granule attributes across scales.…”
Section: Introductionmentioning
confidence: 99%
“…Aikawa et al 14 observed that the applicability of a scale up rule can be case specific. They saw that a constant impeller tip speed approach was valid for scaling up from a mini scale (0.2 L) to pilot scale (11 L), but not between the pilot and commercial scale (200 L).…”
Section: Scale Up Approaches Based On Dimensionless Numbersmentioning
confidence: 99%
“…Even when the equipment from the same manufacturer is used, with the same geometrical properties, the scale-up process of wet granulation can be a challenge [8]. Nevertheless, by developing a progressive design space with a QbD risk based approach, production of pharmaceutical products is robust enough to allow for scale-up adjustments of process parameters [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, responses being observed are usually related to granule properties (particle size distribution [17], porosity [18], size and bulk density [19]). In studies conducted by Aikawa et al [10] and Badawy et al [20] the analyzed responses were tablet properties. Those studies, however, did not utilize machine learning techniques.…”
Section: Introductionmentioning
confidence: 99%